(untitled) (University of Khartoum Engineering Journal, 2022)
This paper presents experimental study of the performance of chisel plow under conditions of central irrigated Schemes. The research was conducted in the Gezira irrigated Scheme at Experimental Field of Gezira University. Mounted 3-rows chisel plows mark RAU and 75 hp Massey Fergusson (GIAD) tractor were used in the experiment. The performance of chisel plow was evaluated by parameters, which included: losses of chiseling process (uncut area); aggregate size distribution; bulk density; soil moisture content; control of weeds and residues; degree of soil surface evenness; draft requirement; fuel consumption; and field capacity. Each of these parameter studied dependent of two parameters: working speed and depth of cut. A loss of uncut areas at critical depth was found to be 12%. The failure zone and overlap area was found to be 31.4 x 11 cm and 0.02 m2 respectively. The later was dependent of the depth. Losses of plowed area were increased to 23% and 31% when depth was increased to 15cm and 20cm respectively. Based on mean weight diameter of soil clod, structure of the soil was improved by 14% when the speed and depth were increased from 3.34 to 5.85km/hr. and from 15cm to 20cm respectively. Soil natural bulk density was found to be 1.45, g/cm3. Bulk density generally was decreased, in such that it decreased in the upper layer (0-10 cm) by 10%, in the middle layer (10-20 cm) by 7%, and in the bottom soil layer (20-30 cm) by only 1 %. Soil moisture content was decreased by 30% at the upper soil layer (0-15cm) during 9 hours only. Weeds and residues leaving at soil surface after chiseling (at 5.58 km/hr. and 20 cm) were found to be 13% and 37%. Degree of the soil level after chiseling was found to be improved by ±14% of the mean value. Draft force increased by 14% when the depth was increased from 15 to 20 cm at constant speed of 5.85 km/hr. Draft force at critical depth changed by 22% when the speed was increased from 3.34 to 5.85 km/hr. Fuel consumption of chisel plow at speeds of 3.34 km/hr and 5.85 km/hr was increased by 17% and 23% respectively when depth increased from 15cm to 20cm in both cases. Machine field capacity and energy consumption increased by 66% and 39% respectively when speed was changed from 3.34km/hr to5.85 km/hr. in both cases.